Unifying theories of programming : 6th International Symposium, UTP 2016, Reykjavik, Iceland, June 4-5, 2016, Revised selected papers /: 6th International Symposium, UTP 2016, Reykjavik, Iceland, June 4-5, 2016, Revised selected papers. (2017) - Unknown
No abstract available